2019
DOI: 10.3390/biom9110644
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology Study of the Multiple Angiogenesis Inhibitor RC28-E on Anti-Fibrosis in a Chemically Induced Lung Injury Model

Abstract: Background: Disease-related injury in any organ triggers a complex cascade of cellular and molecular responses that culminate in tissue fibrosis, inflammation, and angiogenesis simultaneously. Multiple cell angiogenesis is an essential part of the tissue damage response, which is involved in fibrosis development. RC28-E is a novel recombinant dual decoy receptor lgG1 Fc-fusion protein that can block vascular endothelial growth factor (VEGFA), platelet-derived growth factor (PDGF), and fibroblast growth factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Besides accelerating regeneration in the injured liver, FGF signaling also leads to fibrosis development. There is evidence that as a commonly used model of chronic liver injury, carbon tetrachloride (CCl4)-induced liver fibrosis is significantly reduced in FGF1/FGF2-deficient mice (Kou et al, 2019). Consistently, inhibition of FGF signaling blunts inflammatory through restraining activation of the NF-κB signaling cascades in several experimental models for chronic inflammatory diseases (Huang et al, 2019;Qi and Xin, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Besides accelerating regeneration in the injured liver, FGF signaling also leads to fibrosis development. There is evidence that as a commonly used model of chronic liver injury, carbon tetrachloride (CCl4)-induced liver fibrosis is significantly reduced in FGF1/FGF2-deficient mice (Kou et al, 2019). Consistently, inhibition of FGF signaling blunts inflammatory through restraining activation of the NF-κB signaling cascades in several experimental models for chronic inflammatory diseases (Huang et al, 2019;Qi and Xin, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…The second stage is the pulmonary fibrosis stage. Interstitial cell proliferation and matrix collagen aggregation replace normal lung tissue structure (25,26). Studies have shown that the presence of myofibroblasts in fibroblast lesions is one of the histopathological markers of pulmonary fibrosis, which is induced by many chemokines, the most common of which is TGF-β (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative Real time PCR was performed as previously described [ 21 ]. Total RNA was extracted from cultivated cells using Trizol reagent (Thermo Fisher, USA).…”
Section: Methodsmentioning
confidence: 99%